Three dimensional face recognition under occlusion variance - Alyüz, Neşe. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
With advances in sensor technology, three dimensional (3D) face has become an emerging biometric modality, preferred especially in high security applications. However, dealing with occlusions covering the facial surface is a great challenge. In this thesis, we propose a fully automatic 3D face recognition system, attacking three sequential problems: (i) Registration of occluded surfaces, (ii) detection of occluded regions, and (iii) classification of occlusion-removed faces. For the alignment problem, we propose an adaptively selected model based registration scheme, where a model is selected for an occluded face such that only the valid non-occluded patches are utilized in correspondence establishment. After registration, occlusions are detected, where we propose two different occlusion detection approaches. In the first detector, fitness to a pixelwise statistical model of the facial surface is used. In the second approach, in addition to the facial model, neighborhood information is incorporated. For occlusion handling, two different strategies are evaluated: (i) Removal of occlusions, and (ii) restoration of missing parts. In the classification stage, a masking strategy, which we call masked projection, is proposed to enable the use of subspace analysis techniques with incomplete data. Experimental results on two databases with realistic facial occlusions, namely, the Bosphorus and the UMB-DB, confirm that: (i) The proposed registration technique based on the adaptively selected model is a good alternative to obtain occlusion robustness; (ii) in occlusion detection, use of a statistical facial model is beneficial to make a pixelwise decision, which can further be improved by incorporating neighborhood relations to model coherency of surfaces; (iii) restoration provides only an approximation of the surface and is not suitable for classification purposes, (iv) masked projection serves as a viable approach to apply subspace techniques on incomplete data.
Keywords: Human face recognition (Computer science); Three-dimensional display systems.